Impact of scheduling multiple outdoor free-play periods in childcare on child moderate-to-vigorous physical activity: a cluster randomised trial - Razak, Lubna Abdul (Int J Behav Nutr Phys Act, 2018)
BACKGROUND: Increasing the frequency of periods of outdoor free-play in childcare may represent an opportunity to increase child physical activity. This study aimed to assess the efficacy of scheduling multiple periods of outdoor free-play in increasing the time children spend in moderate-to-vigorous physical activity (MVPA) while attending childcare. METHODS: The study employed a cluster randomised controlled trial design involving children aged 3 to 6 years, attending ten childcare services in the Hunter New England region of New South Wales, Australia. Five services were randomised to receive the intervention and five to a control condition. The intervention involved services scheduling three separate periods of outdoor free-play from 9 am to 3 pm per day, each at least 15 min in duration, with the total equivalent to their usual daily duration of outdoor play period. Control services implemented the usual single continuous period of outdoor free-play over this time. The primary outcome, children’s moderate-to-vigorous physical activity (MVPA) while in care per day, was measured over 5 days via accelerometers at baseline and at 3 months post baseline. Secondary outcomes included percentage of time spent in MVPA while in care per day, total physical activity while in care per day and documented child injury, a hypothesised potential unintended adverse event. Childcare services and data collectors were not blind to the experimental group allocation. RESULTS: Parents of 439 (71.6%) children attending participating childcare services consented for their child to participate in the trial. Of these, 316 (72.0%) children provided valid accelerometer data at both time points. Relative to children in control services, mean daily minutes of MVPA in care was significantly greater at follow-up among children attending intervention services (adjusted difference between groups 5.21 min, 95% CI 0.59–9.83 p = 0.03). Percentage of time spent in MVPA in care per day was also greater at follow-up among children in intervention services relative to control services (adjusted difference between groups 1.57, 95% CI 0.64–2.49 p < 0.001). Total physical activity while in care per day, assessed via counts per minute approached but did not reach significance (adjusted difference between groups 14.25, 95% CI 2.26–30.76 p = 0.09). There were no differences between groups in child injury nor subgroup interactions for the primary trial outcome by child age, sex, or baseline MVPA levels. CONCLUSION: Scheduling multiple periods of outdoor free-play significantly increased the time children spent in MVPA while in attendance at childcare. This simple ecological intervention could be considered for broader dissemination as a strategy to increase child physical activity at a population level. TRIAL REGISTRATION: This trial was prospectively registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) (ACTRN1261000347460). Prospectively registered 17th March 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12966-018-0665-5) contains supplementary material, which is available to authorized users.